2000
DOI: 10.1136/vr.147.5.123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory findings in cases of toxic mastitis in cows in Northern Ireland

Abstract: This paper describes the clinical and laboratory findings from 264 cases of toxic mastitis in cows in Northern Ireland between October 1995 and May 1997. Nearly all the cases occurred during the winter housing period, with 84 per cent occurring between November and March inclusive, and 30 per cent in March. Sixty per cent of the cases occurred within one month of calving, and 29 per cent within four days of calving. The most common clinical signs were lethargy (92 per cent), discoloured milk (90 per cent), ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Our study is in agreement with previous studies of cows with experimentally induced and naturally occurring ACM, for which leukopenia, neutropenia, lymphopenia have been reported [3,7]. Smith et al [10] recommended that routine hematological analysis is useful in guiding initial treatment decisions, particularly in valuable cows or when cows are hospitalized.…”
Section: Discussionsupporting
confidence: 83%
“…Our study is in agreement with previous studies of cows with experimentally induced and naturally occurring ACM, for which leukopenia, neutropenia, lymphopenia have been reported [3,7]. Smith et al [10] recommended that routine hematological analysis is useful in guiding initial treatment decisions, particularly in valuable cows or when cows are hospitalized.…”
Section: Discussionsupporting
confidence: 83%
“…Studies on spontaneous or experimental E. coli mastitis have shown that affected cows can be divided into mild or severe responders, based on their clinical signs and disease outcome [8,26,34,35]. Periparturient cows and those in early lactation most frequently show severe clinical signs and even fatal outcome [4,7,18]. The observed systemic and local clinical reactions result from the acute phase reaction (APR), which is the response of the host to any tissue injury caused by trauma or inflammation [32].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the production, function and kinetics of cytokines and APP may explain the varying local and systemic signs of individual cows in E. coli mastitis [3,8,18,20,25]. We used an experimental LPS model to study local and systemic acute phase responses of dairy cows in different lactation stages.…”
Section: Introductionmentioning
confidence: 99%
“…L. monocytogenes has been described as a “ less common cause” of bovine environmental mastitis and may often be associated with the accidental introduction of the organism during intramammary infusion [25]. Mild persistent, antibiotic resistant, low grade infections have been documented in cattle and may result in decreased production from infected mammary tissue over time.…”
Section: Discussionmentioning
confidence: 99%